PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS GAMIFIKASI UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA KATOLIK PADA PESERTA DIDIK KELAS X-1 SMAS ST. IGNASIUS MEDAN - Heber Gimilanta Br Ginting; Monika Handayani Br Ginting; Din Oloan Sihotang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of a gamification-based Problem-Based Learning (PBL) model and to examine the improvement of students' learning outcomes in Catholic Religious Education and Character Education. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 23 students of Class X-1 Phase E at SMAS St. Ignasius Medan in the 2025/2026 academic year. Data were collected through observation, tests, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the gamification-based Problem-Based Learning model effectively improved students' learning outcomes. The average learning outcome score increased from 64 in the pre-action stage to 78 in Cycle I and 88 in Cycle II. Improvements were also observed in the cognitive, affective, and psychomotor domains, as reflected in students' active participation in discussions, problem-solving activities, presentations, and the use of gamification platforms such as Wordwall and Wayground. Therefore, the gamification-based Problem-Based Learning model can be considered an effective approach to improving students' learning outcomes in Catholic Religious Education and Character Education.